High-Flow-Sauerstofftherapie – Schritt für Schritt - Wachs, Christian; Grensemann, Jörn; Kluge, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2020)
In recent years, high-flow oxygen therapy (HFNC) has become established and proven as an oxygenation method for patients with severe respiratory restrictions in most intensive care units. Advantages of this method, which is used especially for patients with hypoxaemia, are the easy application and the compliance by the patient. Devices are used which enable individual oxygen therapy by means of humidification, warming up and gas flow regulation options.
Keywords: mukoziliäre Clearance; Compliance; hyperkapnische respiratorische Insuffizienz; Befeuchterkammer; Gasfluss